Methodology of the Development of a Topical Transdermal Fucoidan Delivery System - E. D. Obluchinskaya; A. N. Shikov; O. N. Pozharitskaya (Разработка и регистрация лекарственных средств, 2023)
Introduction. Marine-derived polysaccharides are promising candidates for the development of innovative drugs. One of such compounds is the polysaccharide fucoidan from brown seaweeds, which shows anticoagulant and anti-inflammatory activity. The development of topical transdermal formulation for the treatment of chronic venous diseases is of particular interest, because with targeted delivery, the active compound in high concentration comes directly to the site where the drug is required, while the risk of side effects is minimal.Aim. Experimental and theoretical justification of the methodological scheme for the development of a transdermal delivery system with fucoidan for local therapy using the Quality by Design (QbD) approach.Materials and methods. Fucoidan was isolated from the thalli of Fucus vesiculosus L. from the Barents Sea according to the original technology of the MMBI RAS. All excipients were approved for medical use. The experiments for rational selection of the excipients for the transdermal delivery system (TSD) were planned using the Greek-Latin square 4 × 4 with repeated observations. The colloidal and thermal stability and pH were evaluated as physicochemical parameters of TSD Structural and mechanical properties of TSD were deter-mined with rotational viscometer. The dissolution rate of fucoidan in vitro was evaluated using the paddle-over-disk method at a temperature of 32 ± 0.5 °C.Results and discussion. The composition and technology of topical TSD цwith fucoidan were developed using the QbD concept. The composition and technology of topical TSD with 15 % of fucoidan as active ingredient were developed. TSD has thermo- and colloidal stability, and has a pH value close to the pH of human skin. Poloxamer 407 was used as a gel base; olive oil was used as a hydrophobic phase. It was found that the ratio of poloxamer 407 to the aqueous phase should be no less than 0.1 and no more than 0.37; the ratio of water to the aqueous phase should not be less than 0.56 and not more than 0.69; and the ratio of polyoxyl 40 hydrogenated castor oil to the oil phase must be at least 0.34. It was found that 9 % poloxamer 407 provides the necessary structural and mechanical properties of TSD. It has been established that the developed TSD of fucoidan with poloxamer 407 belongs to non-Newtonian flow types with plastic properties and has thixotropy.Conclusion. The complex of studies based on QbD approach led to the experimental and theoretical justification of the methodological scheme for the development of a transdermal delivery system with marine polysaccharide fucoidan. The methodological scheme takes into account the physicochemical and technological features of fucoidan and allows you to create a high-quality TSD that ensures stability and complete release of the active substance.